Mandible protrusion and decrease of TMJ sounds: An electrovibratographic examination - Garcia, Alicio Rosalino [UNESP]; Folli, Sérgio [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; de Sousa, Valdir [UNESP] (FapUNIFESP (SciELO), 2008)
This study quantified by, electrovibratography, the amount of mandible protrusion required to decrease significantly temporomandibular joint (TMJ) vibratory energy as an aid in the diagnosis of the recapture of anteriorly displaced disk. Eighteen patients diagnosed as having anterior disk displacement with reduction and TMJ clicking were submitted to electrovibratographic examination at the first appointment and treated with a stabilizing appliance and anterior positioning appliance with 1 to 5 mm protrusion. Vibratory energy was checked in each of these positions. Baseline data were used as control. At the first appointment, the patients had vibrations with more elevated intensities at the middle and late phases of the mouth opening cycle. At only one clinical step, mandible protrusion was obtained with the anterior repositioning appliance, ranging from 1 to 5 mm protusion. At each new position, a new electrovibratographic exam was made. After the 5-mm mandibular projection, only 2 patients presented vibration, with means between 0.6 and 2.8 Hz. Data were analyzed statistically by ANOVA and Tukey's test (α=0.05). The outcomes of this study indicate that 3 mm is the minimum amount of mandible protrusion to significantly decrease the TMJ vibratory energy and to recapture the displaced articular disk.
Keywords: Dental occlusion; Electrovibratography; Temporomandibular joint; Temporomandibular joint disorders; adolescent; adult; body posture; child; dental equipment; dislocation; electrodiagnosis; face pain; female; headache; human; joint characteristics and functions; male; mandible; methodology; otalgia; pathology; pathophysiology; physiology; signal processing; sound; temporomandibular joint; temporomandibular joint disorder; tooth radiography; treatment outcome; vibration; Adolescent; Adult; Centric Relation; Child; Dislocations; Earache; Electrodiagnosis; Facial Pain; Female; Headache; Humans; Male; Mandible; Occlusal Splints; Posture; Range of Motion, Articular; Signal Processing, Computer-Assisted; Sound; Temporomandibular Joint; Temporomandibular Joint Disk; Temporomandibular Joint Disorders; Treatment Outcome; Vibration; Young Adult